2007
DOI: 10.13001/1081-3810.1199
|View full text |Cite
|
Sign up to set email alerts
|

Products of commuting nilpotent operators

Abstract: Abstract. We characterize the matrices that are products of two (or more) commuting square-zero matrices and matrices that are products of two commuting nilpotent matrices. We also give a characterization of operators on an infinite dimensional Hilbert space that are products of two (or more) commuting square-zero operators and operators on an infinite-dimensional vector space that are products of two commuting nilpotent operators.1. Introduction. Is every complex singular square matrix a product of two nilpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The proof by Laffey relies on preceding results by Wu [7]. It was mentioned before [1] that the right factor on p.229, the last factorization [7, Lemma 3], is in fact not nilpotent for certain values of k. Explicitly, the given factorization of Dg[J k (0), J 2 (0)] is invalid for odd k, since the matrix 0 J 2 (0) J k (0) 0 is not nilpotent when k = 7.…”
Section: Problematic Details In the Original Proofsmentioning
confidence: 87%
“…The proof by Laffey relies on preceding results by Wu [7]. It was mentioned before [1] that the right factor on p.229, the last factorization [7, Lemma 3], is in fact not nilpotent for certain values of k. Explicitly, the given factorization of Dg[J k (0), J 2 (0)] is invalid for odd k, since the matrix 0 J 2 (0) J k (0) 0 is not nilpotent when k = 7.…”
Section: Problematic Details In the Original Proofsmentioning
confidence: 87%
“…In Tables 1 and 2 Baksalary characterized all situations in which a linear combination of two idempotent matrices is idempotent, which corresponds to cases (1) and (5) in Table 1. [2] For the remaining solved problems, the readers are referred to [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. For recent advances on this topic and related papers, see [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In [2] it has been shown that an n × n matrix M over an algebraically closed field can be written as a product of two commuting square-zero matrices if and only if M 2 = 0 and rank M ≤ n/4. Also, in [3] it is proven that for any two n × n commuting square-zero matrices A and B over an algebraically closed field, we have rank A + B ≤ n/2.…”
Section: Introductionmentioning
confidence: 99%